Use of penicillin MICs to predict in vitro activity of other beta-lactam antimicrobial agents against Streptococcus pneumoniae. - Brueggemann, A; Pfaller, M; Doern, G (2001)
Linear regression analysis was used to compare penicillin MICs determined with 3,129 recent clinical isolates of Streptococcus pneumoniae to MICs obtained with nine other beta-lactam antimicrobial agents. A strong correlation between penicillin MICs and those obtained with other beta-lactams was demonstrated. It may be possible to test penicillin and use MICs obtained with penicillin to predict MICs of other beta-lactam antimicrobials for Streptococcus pneumoniae.